Comparison study of the counter-flow regenerative evaporative heat exchangers with numerical methods. (5th June 2015) - Pandelidis, Demis; Anisimov, Sergey; Worek, William M.
Abstract: This paper numerically investigates the performance and heat and mass transfer processes that occur in regenerative heat and mass exchangers (HMXs) used for indirect evaporative air cooling. Two basic types of regenerative air coolers were compared: an exchanger with typical airflows arrangement and an exchanger with perforations along the whole length of the dry channel. The numerical model is based on one-dimensional heat and mass transfer assumptions and was validated against existing experimental data. The results obtained from the simulation reveal high effectiveness of the presented unit. The results allow defining optimal geometric and operational parameters for the typical regenerative exchanger and regenerative exchanger with perforations. It was determined that the value of working to main air-flow ratio has a significant impact on the cooling performance of considered air coolers. Highlights: A numerical study of regenerative heat exchangers is presented. The developed ε-NTU model is verified against existing experimental data. Numerical simulations show unique features of the considered exchangers. The optimum ranges of the working to main air-flow ratio are determined.